Online Nuclear Emergency Response System (ONERS) for consequence assessment and decision support in the early phase of nuclear accidents - Simulations for postulated events and methodology validation. (January 2020) - Raja Shekhar, S.S.; Venkata Srinivas, C.; Rakesh, P.T.; Deepu, R.; Prasada Rao, P.V.V.; Baskaran, R.; Venkatraman, B.
Abstract: Online Nuclear Emergency Response System (ONERS) is a comprehensive Decision Support System developed using Open source WebGIS (Geographical Information System) technologies for management of Off-Site Nuclear Emergencies for Nuclear Power Plant sites of India. The system is based on numerical meteorological and dispersion models, weather data and source term estimation using environmental radiation monitors. It simulates the pattern of atmospheric dispersion, concentration, radioactivity fallout, and radiation dose profiles in various pathways around the affected site. The system projects the current and future radiological scenario along with geographical and demographic information and simulates the consequences of atmospheric releases on population by spatial analysis. It also computes counter measures using national regulatory guidelines for suggestion of protective actions to decision makers and first responders. This work presents the salient features of the ONERS, its monitoring network and utility. The methodology of dose projections is tested by performing simulations for a postulated accident and the effectiveness of the system for decision making during emergency scenarios is illustrated for a hypothetical scenario. Graphical abstract: Online Nuclear Emergency Response System (ONERS) projected radiation doses and counter measure analysis for a postulated nuclear accident. Top panels show the Weather Stations, Environmental Radiation monitoring network, GIS & Satellite data and the real-time Meteorological and Dispersion computations on HPC. Side panels show the application of ONERS in Off-Site Emergency Exercises by Decision makers and first responders. Image 1 Highlights: A WebGIS based Decision Support System ONERS is developed for management of off-site nuclear emergencies. System is based on meteorological, atmospheric dispersion and source term models and environmental monitors. Estimates accident consequences with spatial analysis of dose outputs using GIS. Methodology of dose calculation is tested for postulated accidents and utility of system is illustrated.